2020
DOI: 10.3390/su12218804
|View full text |Cite
|
Sign up to set email alerts
|

Does ESG Affect the Stability of Dividend Policies in Europe?

Abstract: Sustainability has become a significant issue for firms and investors throughout the world, although it cannot be attained if policies impact the stability of firms’ dividend policies. In this paper, we use data from the Stoxx Euro 600 firms from 2000 to 2019 and the ESG (environmental, social and governance) scores from Thomson Reuters to assess the relationship between ESG responsibility performances and the firm’s dividend policy. The results indicate that more sustainable firms exhibit a more stable divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 63 publications
(87 reference statements)
4
48
10
2
Order By: Relevance
“…Verga Matos et al [11] extend these conclusions by providing evidence that more sustainable firms will engage better with long term objectives of shareholders and remaining stakeholders, by means of a more stable dividend payout. The authors use data from Stoxx Euro 600 firms.…”
Section: Literature Reviewmentioning
confidence: 83%
“…Verga Matos et al [11] extend these conclusions by providing evidence that more sustainable firms will engage better with long term objectives of shareholders and remaining stakeholders, by means of a more stable dividend payout. The authors use data from Stoxx Euro 600 firms.…”
Section: Literature Reviewmentioning
confidence: 83%
“…Several articles have found that well-performing firms tend to pay higher dividends (A. Hendijani Zadeh, 2020;Limkriangkrai et al, 2017;Verga Matos et al, 2020). It is unclear, therefore, the use of dividends in case of non-mandatory disclosure concerning mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…Institutional investors often associate ESG performance with high-quality risk management (Salama et al, 2011). Overall, ESG scores are known for positively impacting financial risk (Matos et al, 2020) and long-term risk-adjusted returns (Borgers et al, 2015;Shrivastava et al, 2019). ESG practices and disclosures improve financial and reputational risk with investors (Weber, 2014) by enhancing brand loyalty, reducing the cost of capital, maintaining social acceptance, and improving revenues and returns (Arayssi et al, 2020;Camilleri, 2015;Salama et al, 2011).…”
Section: Deductive Content Analysismentioning
confidence: 99%